Activity and safety of metronomic cyclophosphamide in the modern era of metastatic castration-resistant prostate cancer. (19th March 2019) - Caffo, Orazio; Facchini, Gaetano; Biasco, Elisa; Ferraù, Francesco; Morelli, Franco; Donini, Maddalena; Buttigliero, Consuelo; Calvani, Nicola; Guida, Annalisa; Chiuri, Vincenzo Emanuele; Basso, Umberto; Mucciarini, Claudia; et al.
Aim: To evaluate activity of metronomic cyclophosphamide (mCTX) in heavily pretreated metastatic castration-resistant prostate cancer (mCRPC) patients.Patients & methods: We retrospectively evaluated a consecutive series of 74 mCRPC patients treated with at least one new agent after docetaxel failure, who received once-daily oral mCTX treatment at a fixed dose of 50 mg.Results: The treatment was well tolerated. Sixteen percent of the patients experienced a major biochemical response. Median progression-free survival was 4.0 months, and median overall survival was 8.1 months.Conclusions: In the modern context of mCRPC, mCTX may represent a valuable and inexpensive alternative to new agents, which have shown similar activity in heavily pretreated patients.